Eye movement evidence for context-sensitive derivation of scalar inferences - Politzer-Ahles, S; Husband, E (University of California Press, 2017)
A scalar expression like some can optionally have an enriched interpretation (approximately meaning “some, but not all”) depending on the context in which it appears. Numerous experiments using the self-paced reading method have found evidence that context has an online effect on the interpretation of a scalar term, resulting in faster or slower reading times for a later phrase whose comprehension is dependent on the interpretation of some. The present study used eye movements to isolate the time course of this process. We find evidence that the reading time facilitation observed in previous studies was driven by early reading measures, with little reading time evidence for an immediate inference-based processing cost at the scalar expression itself, consistent with previous studies. Our results suggest that comprehenders can rapidly commit to enriched interpretations online without cost and that these enriched interpretations are then used to guide the processing of upcoming sentence material.